S.M. Ali, a commemorative volume - Ali, S. M., 1928-1993.; Ally, Fowzia; Isalāma, Saiẏada Manajurula (Dhaka : S.M. Ali Memorial Committee, 1997)
Collection of editorials, tributes on S.M. Ali, 1928-1993, a journalist from Bangladesh; also includes biographical sketches.
Donated by Rebecca Dipa Khan
Includes a few articles in Bengali.
Keywords: Ali, S. M., -- 1928-1993.; Journalists -- Bangladesh -- Biography